Hubungan Lama Menderita Luka dengan Harga Diri Pasien Diabetic Foot Ulcer - Wulandari, Putri; Diani, Noor; Lestari, Dhian Ririn (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
People with type 2 diabetes mellitus are affected by complications of diabetic foot ulcers. Long suffereddiabetic foot ulcer to heal affected by psychological stress impact on changes in patient self-esteem. Thisstudy analyzed the relationship between suffering duration of wound with self-esteem of diabetic foot ulcerpatients. This research used the correlational method with cross-sectional method. The sampling techniquewas accidental sampling involved 80 patients. Data were analyzed by using Chi-Square test. The resultsshowed majority of patients suffering from diabetic foot ulcer wounds were ≥45 days (57.5%). The majority ofpatients have low self-esteem (52.5%). Chi-Square test results are p-value = 0.049 (α <0.05) with OR =2.756 (95% CI = 1.104-6, 879) which means there was a significant relationship between the length ofsuffering from wound with the patient's self-esteem of diabetic foot ulcer. Suffering duration of wound was afactor that agreed with self-esteem.